Sleep as the threshold of mortality: Death anxiety, insomnia, and the ritual function of yoga - Ni Wayan Jemiwi Jero; Masatoshi Torii; Jimmy Susanto; Mi'rajul Akbar; Ni Luh Putu Dian Yunita Sari (Life and Death: Journal of Eschatology, 2026)
Background: Insomnia is conventionally framed as a clinical and epidemiological burden, yet emerging psychological literature suggests sleep disruption is entangled with death anxiety and mortality salience, where nighttime wakefulness is when the mind's habitual defenses against death-awareness weaken, surfacing existential distress that manifests physiologically as hyperarousal. In Indonesia, where religious and cultural conceptions of death, fate, and the afterlife remain central to everyday meaning-making, insomnia among women, older adults, and the chronically ill may reflect not merely biological dysregulation but unresolved existential confrontation with mortality. This study examines health yoga, historically a contemplative practice oriented toward liberation and confrontation with impermanence, as an intervention addressing this existential dimension of sleep disturbance. Methods: An integrative literature review and conceptual analysis synthesized insomnia epidemiology, Terror Management Theory, and yoga-intervention research, including Indonesian data comparing Yin and Vinyasa yoga among female office workers with mild-to-moderate insomnia. Findings: Yoga improved sleep latency, efficiency, and subjective quality, with Yin yoga outperforming Vinyasa. Mechanistically, yoga reduced sympathetic hyperarousal and cortisol while enhancing parasympathetic activation, which are physiological correlates of reduced death-anxiety arousal. Framed eschatologically, yoga functions as a ritualized practice of mortality acceptance, addressing insomnia's existential root rather than only its somatic symptoms. Conclusion: Health yoga offers a culturally resonant, contemplative response to sleep disturbance understood as a site of unmanaged existential distress, warranting integration into Indonesian public health and meaning-making frameworks alike. Novelty/Originality of this article: This article bridges epidemiological, physiological, and eschatological perspectives on insomnia, positioning yoga as both clinical intervention and mortality-coping ritual.